Content Code Blurring: A New Approach to Content Extraction - Gottron, T. (2008 19th International Workshop on Database and Expert Systems Applications, 2008)
Most HTML documents on the world wide web contain far more than the article or text which forms their main content. Navigation menus, functional and design elements or commercial banners are typical examples of additional contents. Content extraction is the process of identifying the main content and/or removing the additional contents. We introduce content code blurring, a novel content extraction algorithm. As the main text content is typically a long, homogeneously formatted region in a web document, the aim is to identify exactly these regions in an iterative process. Comparing its performance with existing content extraction solutions we show thatfor most documents content code blurring delivers the best results.